AMPK/p38/Nrf2 activation as a protective feedback to restrain oxidative stress and inflammation in microglia stimulated with sodium fluoride. (April 2020) - Song, Chao; Heping, Huangfu; Shen, Yongshu; Jin, Shuangxing; Li, Deyin; Zhang, Aiguo; Ren, Xiaoli; Wang, Kunli; Zhang, Lei; Wang, Jundong; Shi, Dongmei
Abstract: Dysregulated activation of inflammation plays an important role in the development and progression of neuronal damage, and limiting the production of reactive oxygen species (ROS) can suppress the inflammatory signals. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a redox-sensing transcription factor that drives an adaptive cellular defense in response to oxidative stress. However, the implications of Nrf2 in sodium fluoride (NaF)-stimulated microglia and the underlying mechanisms remain obscure. In this study, we demonstrated that NaF activated the Nrf2 signaling and enhanced the downstream antioxidant protein levels, including heme oxygenase-1 and quinine oxidoreductase 1. NaF induced oxidative stress, as indicated by increased ROS level and malondialdehyde content, and reduced superoxide dismutase activity. Moreover, NaF promoted the nuclear translocation of NF-κB, thus increased the production of the pro-inflammatory cytokines tumor necrosis factor-α, interleukin (IL)-6, and IL-1β. However, these effects were relieved by overexpression of Nrf2. Meanwhile, knockdown of Nrf2 by shRNA exacerbated NaF-induced oxidative stress and inflammation in BV-2 cells and primary cultured microglia. Mechanistically, NaF-induced Nrf2 activation is AMPK/p38 dependent, as deletion of AMPK using siRNA blocked the activating effect of NaF on p38 and Nrf2. Notably, treatment of N-Acety-l -Cysteine attenuated AMPK/p38-dependent Nrf2 activation in microglia exposed to NaF. In conclusion, these data demonstrated for the first time that Nrf2 activation exerts a neuroprotective effect on NaF-stimulated redox imbalance and inflammation that is dependent on the AMPK/p38 pathway. Highlights: NaF-stimulated redox imbalance and inflammation. NaF activated the Nrf2 signaling in BV-2 cells and primary cultured microglia. Nrf2 activation exerts a neuroprotective effect on NaF-stimulated redox imbalance and inflammation. ROS-AMPK-p38 signaling is the upstream signaling pathway involved in NaF-induced Nrf2 activation.